PENGARUH EDUKASI GIZI MELALUI SHORT MOVIE DAN CERAMAH TERHADAP PENGETAHUAN TENTANG ANEMIA PADA REMAJA PUTRI DI SMA ISLAM PB SOEDIRMAN - Natasya Zahra (2022)
The presence of anaemia in 2022 is still an prevalent health issue worldwide. Cause by iron (Fe) deficiency, this health issue is also experienced by Indonesians. Purpose: Educating nutritional awareness through short films and lectures about anaemia towards female high school students of SMA Islam PB Soedirman, which are selected through random sampling. Using the Wilcoxon test to determine the difference in results before and after the film and lecture, and using the Mann-Whitney test to observe the effectiveness of both mediums. Results: The study shows that there is a change in understanding towards the effects of media usage to educate nutritional significance by use of short movie (p=0,000) and lecture (p=0,000). The results show that intervention using the short movie is more effective than lecture in raising awareness towards anaemia. Conclusion: the intervention using the short movie is more effective than lecture in raising awareness towards anaemia in female students of SMA Islam PB Soedirman. The short movie is considered more effective based on the average final score which is higher than the lecture group.